1974
DOI: 10.1149/1.2396830
|View full text |Cite
|
Sign up to set email alerts
|

Some Practical Aspects of Electroless Gold Plating

Abstract: The electroless gold plating process using potassium borohydride as the reducing agent has been investigated for impurity effects, material compatibility, bath agitation effects, and thickness uniformity and line resolution in selective plating of patterned substrates. Impurities may cause a decrease in plating rate [Ni(II) ], bath instability [Ni(II), Co(II), Fe(II) ], thickness nonuniformity (polyethylene, organics in deionized water), and nodule formation (some surfactants). Bath agitation is beneficial: it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 4 publications
0
38
0
Order By: Relevance
“…Decomposition of the borohydride and DMAB baths can also occur when they are contaminated with certain organics FIGURE 21.5 Effect of bath contamination with Ni 2 þ and Cu 2 þ ions on plating rate of borohydride bath [5]. IMPROVED BOROHYDRIDE AND DMAB BATHS such as polyethylene [5].…”
Section: Methods Of Improving Bath Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Decomposition of the borohydride and DMAB baths can also occur when they are contaminated with certain organics FIGURE 21.5 Effect of bath contamination with Ni 2 þ and Cu 2 þ ions on plating rate of borohydride bath [5]. IMPROVED BOROHYDRIDE AND DMAB BATHS such as polyethylene [5].…”
Section: Methods Of Improving Bath Stabilitymentioning
confidence: 99%
“…IMPROVED BOROHYDRIDE AND DMAB BATHS such as polyethylene [5]. One should be aware of possibilities of contamination with trace amounts of organic materials from storage bottles and vessels as well as from the water used to prepare the solutions.…”
Section: Methods Of Improving Bath Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…There have been laboratory studies of the electroless plating of the platinum group metals, including palladium, palladium phosphorus, palladium boron, platinum, and ruthenium and rhodium alloys (17). While these may have some …”
Section: En Technology Backgroundmentioning
confidence: 99%
“…The bath composition is given in Appendix 1 (2). We have found that it is convenient to prepare a 5• concentrated solution for storage.…”
Section: Solution Preparation and Plating Proceduresmentioning
confidence: 99%